RECORDS MANAGEMENT AT THE DANAU PANGGANG INPATIENT PUBLIC HEALTH CENTER TECHNICAL IMPLEMENTATION UNIT, HULU SUNGAI UTARA REGENCY - Mukhlis Ikhwana; Saidah Hasbiyah; Barkatullah Barkatullah (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2026)
The purpose of this study is to determine the Archives Management at the Inpatient Health Center UPT Danau Panggang, Hulu Sungai Utara Regency. This study uses a qualitative approach with a descriptive-qualitative research type. The data collection techniques used are interviews, observation and documentation. Data sources were taken through purposive sampling of 11 people. After the data was collected, it was analyzed using data reduction techniques, data presentation and conclusion drawing. The results of the study indicate that Archives Management at the Inpatient Health Center UPT Danau Panggang, Hulu Sungai Utara Regency is not good, First, Human resources include employee skills in archives management is not good, employee training in archives management is quite good, Second, facilities and infrastructure include archival equipment is not good, facilities are not good. Third, the archival system includes the creation of archives is not good, archives reduction is not good. Fourth, archival policies include laws that are quite good, government regulations are quite good. Fifth, funds/budgets include procurement of facilities that are not good, procurement of infrastructure is not good. The sixth socialization and appreciation of records includes providing guidance to less than optimal records officers and providing appreciation for less than optimal employee performance. Inhibiting factors include a lack of facilities and infrastructure, the absence of dedicated employees to manage archives, and the lack of appreciation for employee performance in managing archives. Encouraging factors include the existence of a legal basis and training in records management.